The influence of ESL teachers’ beliefs of teaching and learning on teacher talk / Akindele Abdullahi Ademola - Akindele Abdullahi , Ademola (2018)
This study aims to investigate the beliefs of three Nigerian secondary ESL (English as a Second Language) teachers about teaching and learning of the English language. It also seeks to explore how the beliefs of the teachers influence their language use in the classroom. The theoretical framework for this study is provided by Nespor (1987), Johnson (1994), and Yook (2010). In order to achieve the objectives of the study, a qualitative case study design was employed. Semi-structured interviews, audio-recording, classroom observation and field notes were the instruments used to collect the data of the study. Three ESL teachers in an urban private secondary school provided data of the study. Answers to the guiding research questions were obtained from the analysis of the transcripts of six interviews, six audio recorded lessons, observations and field notes. The findings reveal that the teachers held beliefs about ESL teaching and learning that were consistent with their classroom practices. However, in a few instances, there was incongruence between the teachers’ stated beliefs and classroom practices. Incongruence between their ESL teaching and learning beliefs and practices stemmed from their dominance of classroom communication. The findings of the study show that the teachers’ beliefs about the roles of L1 and L2 influenced their own language use.